Aluminum Oxide Nanoparticle Impact on Plant Growth and Development - Brinkley, Evan (East Carolina University, 2022)
Nanoparticles are becoming increasingly more applicable in science as technological barriers are being broken and more broad uses are being discovered. With this ever increasing research and application of nanoparticles, the need for information on their specific impact as pollutants need to be equally researched. This is the cause for the boom of research on individual species of nanoparticles over the past decade in order to better understand the specific effects on plants and animals alike. Aluminum oxide is widely used commercially and because of that it has a presence as a potential pollutant in the environment. In this study, the impact of nanoparticles, aluminum oxide specifically, on plant growth, development, an gene expression will be monitored over a period of time. Researching and understanding mdore about this nanoparticle’s impact on plant life is grounds for understanding how dangerous it is as a pollutant. Camelina Sativa is a flowering oilseed plant native to Europe and Central Asia. This study aims to methodically test varying concentrations of Aluminum Oxide effect on a large sample of Camelina Sativa seeds as they grow. This protocol will minimize any impact of contamination while closely monitoring germination rates, root and plant length, biomass, number of leaves, and gene expression. The experiment itself is compatible with most nanoparticles anytime of year since conditions are constant and agar plates are produced on site.
Keywords: Nanoparticle Pollution, Aluminum Oxide Toxicity, Plant and Seed Germination